The Relationship Between Husband's Knowledge And Selection Of Vasectomy Contraceptive Methods - Riza umami (Jurusan Kebidanan Poltekkes Kemenkes Sorong, 2022)
Vasectomy is a method with smallest amount of user amongs contraception. This phenomenon happened because most of husbands have poor knowledge about vasectomy, it links with wrong perceptions and views surrounding vasectomy such as vasectomy is a catration procedure, vasectomy is causing sexual disfungsion, and vasectomy degrades libido. This study aims to identificate relationship of men’s knowledge with vasectomy choosing. This study is a literature review study specifically traditional literature review. Articles was selected from two databases: google schoolar and DOAJ. We took the articles from two databases than screen them using PEOS framework and claimed 10 articles containing 8 national articles and 2 international articles. Ten articles show that most of men or husbands had poor knowledge about vasectomy. Meanwhile, most of men or husbands did not choose vasectomy as the contraception methods. All articles provide that there is relationship between husband’s knowledge and vasectomy choosing. Knowledge is a predisposing factor of vasectomy choosing, so an adequate counseling is needed to boost husband’s knowledge. Health provider should upgrade the skill of communication, information, and education to prevent wrong views and perceptions about vasectomy among husbands.